Light generated bubble for microparticle propulsion - Ido Frenkel (Nature Portfolio, 2017)
Abstract Light activated motion of micron-sized particles with effective forces in the range of micro-Newtons is hereby proposed and demonstrated. Our investigation shows that this exceptional amount of force results from accumulation of light-generated heat by a micron-sized particle that translates into motion due to a phase transition in the nearby water. High-speed imagery indicates the role of bubble expansion and later collapse in this event. Comparing observations with known models reveals a dynamic behavior controlled by polytropic trapped vapor and the inertia of the surrounding liquid. The potential of the proposed approach is demonstrated by realization of disordered optical media with binary light-activated switching from opacity to high transparency.